Assessment of Fumman Agricultural Products Industries’ Contract Farming Scheme among Pineapple Fruit Farmers in Oyo State, Nigeria - Yekinni, Oyedeji Taofeeq; Ladigbolu, Temitope Adejoju; Akanji, Ezekiel Olalekan (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
This study assessed FUMMAN Agricultural Products Industries Plc. contract farming scheme among pineapple fruit farmers in Oyo State, Nigeria. Data on enterprise characteristics, benefits derived, constraints encountered and field personnel characteristics were gathered from 105 pineapple fruit farmers. Respondents were sampled using a multistage sampling procedure and interview schedule were used to elicit information which were analyzed using frequencies, percentages, mean, standard deviation and Pearson Product Moment Correlation (PPMC) at α0.05. Findings showed that the majority (76.2%) of the pineapple fruit farmers cultivated less than 1 hectares farm size. They derived benefits from access to stable market (x ̅=1.94) and reduction of wastage level (x ̅=1.84), while defaulting in contractual agreements (x ̅=1.45) and delay in payment (x ̅=1.38) were major constraints encountered. Integrity (x ̅=3.29), honesty (x ̅=3.29) and trustworthiness (x ̅=3.27) were the major characteristics of field personnel identified. There were significant relationships among farmers’ benefit derived (r=0.787), constraints encountered (r=-0.193) and field personnel characteristics’ assessment. It is recommended that FUMMAN should endeavour to keep to contractual agreements while ensuring extension of the contracts through highly rated field personnel